2009
DOI: 10.2337/db08-0260
|View full text |Cite
|
Sign up to set email alerts
|

Xenin, a Gastrointestinal Peptide, Regulates Feeding Independent of the Melanocortin Signaling Pathway

Abstract: OBJECTIVE-Xenin, a 25-amino acid peptide, was initially isolated from human gastric mucosa. Plasma levels of xenin rise after a meal in humans, and administration of xenin inhibits feeding in rats and chicks. However, little is known about the mechanism by which xenin regulates food intake. Signaling pathways including leptin and melanocortins play a pivotal role in the regulation of energy balance. Therefore, we addressed the hypothesis that xenin functions as a satiety factor by acting through the melanocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 31 publications
5
41
1
Order By: Relevance
“…Consistent with earlier reports (Cline et al 2007, Nandar et al 2008, Cooke et al 2009, Leckstrom et al 2009 we were able to demonstrate a satiety effect of xenin in normal mice. The dose required to induce such effects was high (500 nmol/kg), but this is in agreement with others (Leckstrom et al 2009).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with earlier reports (Cline et al 2007, Nandar et al 2008, Cooke et al 2009, Leckstrom et al 2009 we were able to demonstrate a satiety effect of xenin in normal mice. The dose required to induce such effects was high (500 nmol/kg), but this is in agreement with others (Leckstrom et al 2009).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, xenin is now thought to be involved in the regulation of calorie intake (Leckstrom et al 2009) and possibly insulin secretion (Silvestre et al 2003). Thus, the aim of the current study was to evaluate the effects and role of xenin in food intake, glucose homoeostasis and insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lack of in vivo biological action of the fragment peptides was mirrored by studies examining feeding behaviour, as we were unable to demonstrate any satiety effects in normal mice. Consistent with earlier reports (Cline et al 2007, Cooke et al 2009, Leckstrom et al 2009), a mild satiating effect of native xenin-25 was observed in vivo, corroborating use of this model to investigate the biological actions of xenin-25 fragment peptides. Indeed, it has recently been shown that xenin-25 induces appetite-suppressive effects through delayed gastric emptying and activation of cells in the nucleus of the solitary tract (Kim & Mizuno 2010).…”
Section: Discussionsupporting
confidence: 91%